Tea or tears: online teaching during the COVID-19 pandemic. Issue 2 (15th March 2021) - Teng, Mark Feng; Wu, Junjie Gavin
ABSTRACT: This report describes two teachers' challenges and coping strategies while teaching online following the suspension of face-to-face classes due to the COVID-19 pandemic. Findings shed light on proactive and passive agency. This study also provides an understanding of teachers' 'tea or tears' in online teaching.